Implementation of Regenerative Thermal Oxidation Device Based on High-Heating Device for Low-Emission Combustion - Hoon-Min Park; Dal-Hwan Yoon; Joon-Seong Lee; Hyun-Min Jung; Dae-Hee Lee; Dong-Hwan Jeon; Tae-Yeung Lim (Energies)
In this paper, a heating device is implemented by considering two large factors in a 100 cmm RTO design. First, when the combustion chamber is used for a long time with a high temperature of 750–1100 °C depending on the high concentration VOC gas capacity, there is a problem that the combustion chamber explodes or the function of the rotary is stopped due to the fatigue and load of the device. To prevent this, the 100 cmm RTO design with a changed rotary position is improved. Second, an RTO design with a high-heating element is implemented to combust VOC gas discharged from the duct at a stable temperature. Through this, low-emission combustion emissions and energy consumption are reduced. By implementing a high heat generation device, the heat storage combustion oxidation function is improved through the preservation of renewable heat. Over 177 h of demonstration time, we improved the function of 100 cm by discharging 99% of VOC’s removal efficiency, 95.78% of waste heat recovery rate, 21.95% of fuel consumption, and 3.9 ppm of nitrogen oxide concentration.